THE MORAL-PSYCHOLOGICAL SUPPORT TO THE DEFENCE FORCES OF A STATE: PEDAGOGICAL ASPECT - Aleshchenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
This article is dedicated to the research of the pedagogical content of forming the essence of further development of the moralpsychological support of the defense forces of a state at the modern stage of development. Based on experience it’s possible to state that the absence of a clear unified command of the activity of the mentioned structures taken into consideration the peculiarities of functioning of defense forces and the exercise of tasks set, significantly decreases the effectiveness of the system of moral-psychological support; the absence of a unified interbranch trainingprocedure of defense forces, the absence of a state order to train staff on the basis of higher military educational facilities of the Ministry of Defense of Ukraine at an operative and strategic level; the outdating and inperfection of technologies and methodologies of assessment and prognosis of social-psychological conditions of establishing, supporting and renewing the moral-psychological state of the defense staff; the absence of unified views on the concordance of the privileges and social guarantees to NATO criteria; the non-concordance of the current state of the material-technical base of the moral-psychological support to the modern demands and needs of defense forces. There’s a thorough analyses presented on the project of the Concept, as a result of which it has been determined that on a conceptual level there’s no unified normative document in this particular field on the overall support and that the developed concept generally meets the main Provisions of the Doctrine on implementing the defense forces of a state. It has been stipulated that the effective use of the moral-psychological support to the defense forces can be possible only on the basis of nation- wide political constructions, thoroughly developed programs and the involvement of the bodies of national and military authority at all levels. There have been made certain remarks and suggestions on the pedagogical element in the general content of the project Concept that is to be considered when preparing its final variant.